2007
DOI: 10.1002/pits.20217
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the series—personality assessment: The whole and its parts

Abstract: How is information about personality integrated in a comprehensive assessment for children? This is the general issue addressed by this topical volume. The assessment of children's personality is complicated by incomplete frameworks for understanding how the plethora of socioemotional variables fit together within the construct of personality. Many challenging questions persist about how the variables subsumed within the personality rubric relate to each other in the course of development and about how they jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Although the RIM does not determine the presence of psychopathy, it provides unique information that complements PCL: YV findings (Gacono, 1998). This combination of attitudinal/behavioral (i.e., PCL: YV) and performance-based measures (i.e., RIM) helps the clinician to understand the relationship between what an individual says (e.g., “I can control myself”) and what they actually do (Teglasi, 2007). Together, these instruments assess an individual’s problem-solving approach, personality traits, and aggressive acts.…”
Section: The Pcl: Yv and Rim With Children And Youthmentioning
confidence: 99%
“…Although the RIM does not determine the presence of psychopathy, it provides unique information that complements PCL: YV findings (Gacono, 1998). This combination of attitudinal/behavioral (i.e., PCL: YV) and performance-based measures (i.e., RIM) helps the clinician to understand the relationship between what an individual says (e.g., “I can control myself”) and what they actually do (Teglasi, 2007). Together, these instruments assess an individual’s problem-solving approach, personality traits, and aggressive acts.…”
Section: The Pcl: Yv and Rim With Children And Youthmentioning
confidence: 99%
“…Thus, if the goal of psychological assessment is to promote effective intervention, then the usefulness of the FFPI-C may be limited to a small percentage of students. Although research has demonstrated that socioemotional variables predict academic progress and intervention effectiveness (Teglasi, 2007), the utility of the FFPI-C for these purposes has yet to be empirically demonstrated.…”
Section: Assessment For Effective Interventionmentioning
confidence: 99%
“…the understanding of socioemotional, behavioral, and educational problems of students (Knoff, 2002). Socioemotional functioning should be addressed even when concerns about a student are principally academic because students with learning difficulties often demonstrate deficits in socioemotional skills and socioemotional variables predict academic progress (Teglasi, 2007). Further, school psychologists should consider using personality assessments because student strengths identified in these assessments can impact the effectiveness of intervention (Flanagan, 2007).…”
mentioning
confidence: 99%